Teatro de rua, mídia e folkcomunicação: um estudo da Companhia Teatral Arte Viva de Santa Cruz (RN) - Paiva, Beatriz Lima de (2019)
It investigates the occurrences of the communicational and mediatic processes of the street theater of Companhia Teatral Arte Viva (Santa Cruz, Rio Grande do Norte, Brazil), its representative characteristics, and the social interaction between the Company and the public. The report highlights the observation of an original phenomenon: the Company's resistance and representativeness in association with its media contextualization. It approaches the expression of a theatricality that occupies the public space and demonstrates, in its essence, the vocation. The contextualizations related to the folk-communication theory are analyzed (BELTRÃO, 1980, 2001, 2013), (MARQUES DE MELO, 2007, 2008), to the Media Activism (TRIGUEIRO, 2007; 2008) and to the studies focused on Southern Epistemologies (SANTOS, 2006, 2007, SANTOS and MENESES, 2010). The proposal of a methodological strategy used to construct the text is based on interviews with its representatives, the public, the company's presentations, photographic and video records, bibliographic research and consultation of its documentary collections from May 2017 to july 2019.